Combination of culture-dependent and culture-independent molecular methods for the determination of lactic microbiota in sucuk - Kesmen, Z.; Yetiman, A. E.; Gulluce, A.; Kacmaz, N.; Sagdic, O.; Cetin, B.; Adiguzel, A.; Sahin, F.; Yetim, H. (ELSEVIER, 2012)
In this study, the culture-dependent and culture-independent molecular methods were used for the identification of lactic acid bacteria (LAB) in sucuk a Turkish fermented dry sausage. On the one hand, the PCR-DGGE method targetting the V1 and V3 regions of 16S DNA was applied to DNA that was directly extracted from sucuk samples. On the other hand, rep-PCR fingerprinting was performed for the primary differentiation and grouping of the isolates, and the results were confirmed by sequencing of the 165 rDNA and 16S-23S rDNA intergenic spacer region. As a result of the PCR-DGGE analysis of all the samples, total 8 different lactic acid bacteria were identified, and Lactobacillus sakei, Lactobacillus curvatus and Weissella viridescens were the dominant microbiota among these bacteria. The culture-dependent approach indicated that the majority of the strains belonged to the Lactobacillus genera including Lb. sakei, Lactobacillus plantarum, Lb. curvatus, Lactobacillus brevis, Lactobacillus farciminis and Lactobacillus alimentarius. However, Leuconostoc and Weisella were also detected as minor genera. Again, Lactococcus piscium, Weissella halotolerans, Staphylococcus succinus and the comigrated Staphylococcus piscifermentans/Staphylococcus condimenti/Staphylococcus camosus group were detected only with the culture-independent method while Lb. plantarum, Leuconostoc mesenteroides and Leuconostoc citreum were identified only by using the culture-dependent method. In the results, it was concluded that the combination of culture-dependent and culture-independent methods was necessary for reliable and detailed investigation of LAB communities in fermented food products. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Sucuk; Lactic acid bacteria; PCR-DGGE; Sequencing rep-PCR; 16S RIBOSOMAL-RNA; BACTERIAL POPULATION-DYNAMICS; NATURALLY FERMENTED SAUSAGES; PCR-DGGE ANALYSIS; ACID BACTERIA; STARTER CULTURES; DRY SAUSAGE; IDENTIFICATION; LACTOBACILLUS; QUALITY; Food Science & Technology; Microbiology